Effects of thermal aging on transformation temperatures and some physical parameters of Cu-13.5 wt.%Al-4 wt.%Ni shape memory alloy - Balo, S. Nevin; Sel, Neslihan (Elsevier Science Bv, 2012)
The effects of thermal aging at a constant temperature above A(f) (austenite phase finish temperature) on the martensitic transformation of the CuAlNi shape memory alloy were investigated. The evolution of the transformation temperatures was studied by differential scanning calorimetry (DSC). It was found that the thermal aging at a constant temperature above A(f) has a complex effect on the transformation parameters of the CuAlNi shape memory alloy. The M-s, M-f, A(s), and A(f) transformation temperatures were shifted by the thermal annealing. The thermodynamic parameters such as Gibbs free energy and the elastic strain energy of the alloy experienced a decreasing tendency with increasing the aging time. The structural properties of aged alloy samples were studied by X-ray diffraction measurements at room temperature. It was found that the phase transformation parameters of the alloy are controlled by the crystallite size effect. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Shape memory; Gibbs free energy; Elastic strain energy; Vickers hardness